Feasibility trial of an unsupervised, facility-based exercise programme for depressed outpatients. Issue 3 (16th March 2019) - Patten, Christi A.; Vickers, Kristin S.; Lewis, Beth A.; Finnie, Steven B.; Wheeldon, Theresa J.; Decker, Paul A.; Stevens, Susanna; Hathaway, Julie C.; Reese, Michael M.; Seime, Richard J.
ABSTRACT: This pilot study examined feasibility of an unsupervised, facility-based exercise programme for promoting exercise adherence among depressed adult outpatients. The potential effect of adding physical activity counselling on depressive symptoms and physical activity was also explored. Participants were randomly assigned to a 12-week programme comprising an orientation and access to fitness centre resources (control, n = 18) or that programme plus 6 physical activity counselling sessions (intervention, n = 18). Outcome measures were feasibility (fitness centre attendance over 12 weeks); Beck Depression Inventory (BDI-II) and International Physical Activity Questionnaire (IPAQ) completed at baseline and week 12; and qualitative programme feedback. Fitness centre attendance averaged only 12 days (14% of all possible days) with no differences between study groups. No group differences were found on IPAQ or BDI-II scores at week 12. Increases from baseline in IPAQ moderate/vigorous activity minutes were associated with decreases in BDI-II scores at week 12 (p < 0.001). The most helpful programme aspect reported was connecting participants to fitness centre resources. In this pilot study of depressed outpatients, an unsupervised fitness centre based program was not feasible for promoting exercise adherence and adding physical activity counselling was not useful for increasing physical activity levels or reducing depression.